ECOLOGICAL PECULIARITIES OF PINE MOTH (DENDROLIMUS PINI L.), ITS DISTRIBUTION IN THE CHERKASY REGION - Drozda, V. F.; Karpovich, M. S. (Forestry and Forest Melioration, 2018)
Type and intensity of pine colonizaion by pine moth was investigated. Duration of oviposition by pine moth females is 30–35 days, the most intensive – 5–7 days. The main part of eggs is oviposited on healthy and weakened trees (І and ІІ categories of sanitary condition) both at the edge and inside the forest. In the frame of crown the most part of egg masses is oviposited in the lower layer. Eggs of pine moth are parasitized by Trichogramma pintoi Voeg. and Telenomus verticillatus Kieffer. Presented data show the expediency to release laboratory culture of Trichogramma to control pine moth.